Pengaruh Celebrity endorser dan Iklan Produk Terhadap Brand awareness Produk Scarlett Whitenin di Surabaya - Eka Amelia Puspita; Siti Ning Farida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of the research is to see the influence of celebrity endorsers and product advertising on Scarlett Whitening brand awareness. The selected population is Scarlett Whitening users in Surabaya and have purchased and used Scarlett whitening products. The sample was taken from 100 respondents who were consumers of Scarlett whitening products in Surabaya. The sampling technique uses a non-probability sampling technique with a purposive sampling approach. The type of research is associative research with a quantitative approach. Hypothesis testing includes Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Test, t Test, f Test and Coefficient of Determination Test. The research results show that celebrity endorsers and product advertisements simultaneously have a positive and significant effect on brand awareness by obtaining a fcount of 19.866. Meanwhile, partially, the two independent variables have a positive and significant effect on brand awareness by obtaining Celebrity Endorser tcount of 4.546 and product advertising tcount of 4.431.